Application of Population Data Collection in Padasuka Village, Bandung Regency, Based on Website - Zari Yoga HDP, M; Aulia Zidane, Gala; Pradita Hartaman, Reyhan (Universitas Komputer Indonesia, 2022)
Padasuka Sub-region in Cimenyan District, Bandung Regency tries to give populace organization and common enlistment administrations to the local area as per the standards of the Service Standard Guidelines. To work on the nature of administration, it is important to have an assistance framework in the kelurahan so it can work with the presentation of specialist co-ops in sub-district and further develop the help nature of the mechanical assembly into a modernized framework and work with information assortment/chronicling of populace organization. information. The subsequent framework can be utilized to perform automated information assortment